1994
DOI: 10.1063/1.113078
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the photoluminescence intensity of ordered and disordered In0.48Ga0.52P

Abstract: The integrated photoluminescence (PL) intensities of both ordered and disordered epilayers of InGaP grown on GaAs have been measured as a function of temperature. The highest PL efficiency occurs in the most disordered sample. We find that the PL intensities can drop from 2 to almost 4 orders of magnitude between 12 and 280 K. The samples show an Arrhenius behavior characterized by two activation energies. Below 100 K the activation energies lie in the region of 10–20 meV. Above 100 K the activation energy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 11 publications
5
51
0
Order By: Relevance
“…Although the activation energies are uniquely determinated, using the expression ͑2͒, factors A and B are not uniquely determinated and must be interpreted with some caution. 32,34 However, they provide some indication of the relative efficiency of the two mechanisms within a given sample. We observed that the ratio of the number of nonradiative type A centers ͑high activation energy͒ to the number of type B centers ͑low activation energy͒ increases with increasing N concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Although the activation energies are uniquely determinated, using the expression ͑2͒, factors A and B are not uniquely determinated and must be interpreted with some caution. 32,34 However, they provide some indication of the relative efficiency of the two mechanisms within a given sample. We observed that the ratio of the number of nonradiative type A centers ͑high activation energy͒ to the number of type B centers ͑low activation energy͒ increases with increasing N concentration.…”
Section: Resultsmentioning
confidence: 99%
“…This behaviour corresponds to the thermal activated non-radiative recombination mechanism, where the slopes of the dotted line give the activation energy (DE). The PL emission (efficiency) can simply be described by a model involving nonradiative process [6], h(T) ¼ [1 þ (P nro /P r ) exp (ÀDE/k B T)] À1 , where k B is the Boltzmann constant, T is the sample temperature. P nro /P r is effectively the ratio of non-radiative to radiative recombination probability for the loss mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The PL intensity decreases with increasing temperature, indicating the presence of non-radiative recombination centres. The experimental data is fitted to a formula involving one non-radiative recombination process (dotted lines) [8]: I(T) = 1/(1 + (P NR /P R ) exp (-E A /k B T)), where P NR /P R is the ratio of the non-radiative to radiative recombination probability, T is the temperature, k B is the Boltzmann's constant, and E A is the activation energy. An increase in the thermal activation energy with increasing Mg content (from 24 meV for Zn 0.5 Cd 0.5 Se to 108 meV for Mg 0.53 Zn 0.27 Cd 0.2 Se) is observed.…”
Section: Introductionmentioning
confidence: 99%